Prevalence of Urinary Tract Infection during Pregnancy at Tertiary Care Hospital: A Cross-Sectional Study - Amina Begum, Asma Jabeen, Rizwana Lakho, Zakia Zaheen, Madhu Bala, Arooba Bhutto (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: the aim of this study was to determine the prevalence of urinary tract infection during pregnancy and the microorganism associated with it. Study design: A cross-sectional study Place and Duration: This study was conducted at CDF Hospital Hyderabad, Pakistan from June 2020 to June 2021 Methodology: A total of 150 women were included in this study. All the women were pregnant and aged between 18 to 50 years. Urine samples were collected from all the participants. From each sample, bacteria were isolated, and then the isolated bacteria were stained. Also, indole test, catalase test, voges proskauer test, urease test, citrate utilization test, methyl-red test, and coagulation test were performed for the identification of the bacteria. Results: The results of this study showed that almost 16 percent of pregnant women had urinary tract infections. Women aged from 20 years to 30 years showed a higher incidence of urinary tract infection. Urinary tract infection was more prevalent in unemployed participants than in employed participants. In the same way, participants belonging to rural areas had a higher urinary tract infection rate as compared to patients belonging to urban areas. Educated women showed less incidence of UTI as compared to uneducated or less educated women. The results also showed that the women in the third trimester of their pregnancy had the highest prevalence of UTI. Escherichia coli was the most common cause of UTI in our study. The least common cause of UTI was Staphylococcus epidermidis. Conclusion: This study concluded urinary tract infection is one of the most common complications during the gestational period.